THE INFLUENCE OF SHARIA FINANCIAL LITERACY ON INTERST IN USING SHARIA DIGITAL WALLETS - Bella Findayani; Hawiwin Fitriah (Assets Journal: Journal of Economic and Business, 2026)
The rapid development of digital technology has transformed the financial services sector and accelerated the adoption of digital payment systems worldwide. One of the most significant innovations in this field is the digital wallet, which enables users to conduct financial transactions quickly, efficiently, and conveniently through mobile applications. Along with the growth of the digital economy, Sharia digital wallets have emerged as an alternative payment solution that integrates technological innovation with Islamic financial principles. Despite the increasing availability of Sharia-compliant digital payment services, their adoption remains relatively limited compared to conventional digital wallets. One factor that may influence consumers’ willingness to use Sharia digital wallets is the level of Islamic financial literacy. Therefore, this study aims to analyze the effect of Islamic financial literacy on consumers’ interest in using Sharia digital wallets. This study employs a quantitative research approach using a survey method. The research population consists of Muslim consumers who are familiar with digital payment services, while the sample is selected through purposive sampling techniques. Primary data are collected through questionnaires distributed online and measured using a five-point Likert scale. The collected data are analyzed using descriptive statistics and simple linear regression to examine the relationship between Islamic financial literacy and consumers’ interest in using Sharia digital wallets. The findings indicate that Islamic financial literacy has a positive and significant effect on consumers’ interest in using Sharia digital wallets. Consumers with a higher understanding of Islamic financial principles, including the prohibition of riba, gharar, and maysir, tend to demonstrate stronger intentions to adopt Sharia-compliant digital payment service.